Effect of local structural distortions on magnetostructural transformation in Mn3SnC - Dias, E. T.; Priolkar, K. R.; Das, A.; Aquilanti, G.; Cakir, O.; Acet, M.; Nigam, A. K. (IOP Publishing Ltd, 2015)
In this paper we attempt to understand the different nature of first order magnetic transformation in Mn3SnC as compared to that in Mn3GaC. The transformation in Mn3SnC is close to room temperature (T-t approximate to 280 K) and is associated with a large change in magnetic entropy that makes it a suitable candidate for applications in ferroic cooling. Using a combination of x-ray and neutron diffraction and x-ray absorption fine structure spectroscopy we infer that the magnetic ground state consisting of antiferromagnetic and ferromagnetic Mn atoms is due to structural distortions present in Mn6C octahedra.
Keywords: antiperovskites; EXAFS; neutron diffraction; MAGNETIC ENTROPY CHANGE; Physics